Therapies targeting triple-negative breast cancer: a perspective on anti-FGFR - Chen, Jinhao; Wang, Qianru; Wu, Hongyan; Huang, Xiaofei; Cao, Chunyu (Frontiers in Oncology, 2025)
Triple-negative breast cancer (TNBC) is one of the subtypes with the worst prognosis due to tumour heterogeneity and lack of appropriate treatment. This condition is a consequence of the distinctive tumour microenvironment (TME). The TME is associated with factors such as the promotion of proliferation, angiogenesis, inhibition of apoptosis, suppression of the immune system and drug resistance. Therefore, remodelling the TME is critical for the treatment of TNBC. A key role in the formation of the TME is played by the fibroblast growth factor/fibroblast growth factor receptor(FGF/FGFR) signalling pathway. Thus, the FGFRs may be a potential target for treating TNBC. Over-activated FGFRs promote growth, migration and drug resistance in TNBC by influencing the onset of TME events, tumour angiogenesis and immune rejection. A thorough comprehension of the FGF/FGFR signalling pathway’s mechanism of action in the development of TNBC could offer valuable insights for discovering new therapeutic strategies and drug targets. Inhibiting the FGF/FGFR axis could potentially hinder the growth of TNBC and its drug resistance by disrupting crucial biological processes in the TME, such as angiogenesis and immune evasion. This review evaluates the potential of inhibiting the FGF/FGFR axis as a strategy for treating TNBC. It explores the prospects for developing related therapeutic approaches. This study explores the research and application prospects of the FGF/FGFR axis in TNBC. The aim is to provide guidance for further therapeutic research and facilitate the development of innovative approaches targeting TNBC.